Carbon Capture and Mechanical Design of Membrane Reactors: A Systematic Review and Design-Performance Framework for Sustainable Energy Systems - Abdulrahman B. GAMBO (FUDMA Journal of Engineering and Technology, 2026)
The imperative to mitigate climate change has accelerated the development of effective carbon capture systems. Of these, membrane reactors (MRs) have become a promising alternative because they can combine chemical reaction and selective separation of gases in a single unit and thus, they are more efficient and with lower energy penalties. This paper gives an in-depth overview of polymeric, ceramic, and mixed-matrix membranes (MMMs), especially focusing on the mechanical design issues, pressure tolerance, sealing integrity, thermal stress control, and modular scalability, that determine the feasibility of reactors at large scale. A systematic literature review and comparative analysis were performed, resulting in the development of a novel design–performance matrix linking membrane material properties with reactor mechanical requirements. Results demonstrate that ceramic membranes provide superior thermal stability and CO₂ selectivity but are constrained by brittleness, while MMMs balance permeability and durability but face interfacial and scale-up challenges. The study concludes that optimal deployment of membrane reactors requires co-optimization of material innovation and mechanical engineering design, supported by emerging approaches such as additive manufacturing, defect-tolerant sealing, and digital twin models for predictive maintenance. These results point at the importance of interdisciplinary innovation to attain scalable and sustainable carbon capture technologies.
Keywords: Carbon capture; Membrane reactors; Mechanical design; Mixed-matrix membranes; Sustainability.